The Middle East : - Fisher, Sydney Nettleton (McGraw-Hill Company, Inc., 1997)
Praised for its straightforward and accessible style, this text provides a general introduction to the chief elements in Middle Eastern history, allowing readers to proceed into more specialized topics and themes with a solid understanding of the most current scholarship in the field..